Fibroblast growth factor-21 restores insulin sensitivity but induces aberrant bone microstructure in obese insulin-resistant rats - Charoenphandhu N. (2017)
© 2016, The Japanese Society for Bone and Mineral Research and Springer Japan. Fibroblast growth factor (FGF)-21 is a potent endocrine factor that improves insulin resistance and obesity-associated metabolic disorders. However, concomitant activation of peroxisome proliferator-activated receptor-γ by FGF-21 makes bone susceptible to osteopenia and fragility fracture. Since an increase in body weight often induced adaptive change in bone by making it resistant to fracture, it was unclear whether FGF-21 would still induce bone defects in overweight rats. Therefore, the present study aimed to investigate bone microstructure and its mechanical properties in high fat diet (HF)-fed rats treated with 0.1 mg/kg/day FGF-21. Eighteen male rats were divided into two groups to receive either a normal diet or HF for 12 weeks. HF rats were then divided into two subgroups to receive either vehicle or FGF-21 for 4 weeks. The results showed that HF led to obesity, dyslipidemia and insulin resistance, as indicated by hyperinsulinemia with euglycemia. In HF rats, there was an increase in tibial yield displacement (an indicator of ability to be deformed without losing toughness, as determined by 3-point bending) without changes in tibial trabecular volumetric bone mineral density (vBMD) or cortical bone parameters, e.g., cortical thickness and bone area. FGF-21 treatment strongly improved the metabolic parameters and increased insulin sensitivity in HF rats. However, FGF-21-treated HF rats showed lower yield displacement, trabecular vBMD, trabecular bone volume, trabecular thickness, and osteoblast surface compared with vehicle-treated HF rats. These findings suggest that, despite being a potent antagonist of insulin resistance and visceral fat accumulation, FGF-21 is associated with bone defects in HF rats.